Public Perception and Preparedness to Fight Against the Third Wave of COVID-19 in Kabul, Afghanistan - Arash Nemat MD; Farah Yasmin MBBS; Mohammad Yasir Essar DMD; Nahid Raufi MD; Shoaib Ahmad MBBS; Abdullah Asady MD; Qingchun Zeng PhD (SAGE Publishing, 2022)
The avalanche of Corona Virus 2019 (COVID-19) cases has placed an unprecedented load on Afghanistan's government and public health authorities, putting the country in jeopardy. The primary goal of this research was to shed light on the country's capital, Kabul, and to examine the existing preparedness and perceptions of its population in the midst of COVID-19's third wave, which could result in decentralization and fragmentation of the already overburdened health-care system. An online, cross-sectional survey was conducted by the lecturers of the Kabul University of Medical Sciences between April 15, 2021 and April 25, 2021, to evaluate the preparedness of the Kabul citizens amidst the third wave of COVID-19. About 1736 citizens from Kabul participated in the survey. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 25. All categorical variables were reported using frequencies and percentages. The findings revealed that the most common source of COVID-19-related information was social media (74.8%). In addition, 34.4% of subjects had previously been infected with COVID-19. It was reassuring to see that 78.4% of residents said they knew more about COVID-19 than they did about prior COVID-19 waves. A majority (81.5%) expressed willingness to resist the third wave, but 89.4% said that the country's government would be unable to develop an effective COVID-19 vaccine within the next 6 months. The findings of this present study indicates that citizens of Kabul are active in obtaining accurate information and disseminating it in the community. The citizens also reported sufficient COVID-19 related knowledge; however, they were more motivated to fight against the third wave of COVID-19. In regards to vaccination, they believed that the government could not vaccinate the public anytime soon. Hence, the enactment of non-pharmaceutical measures is important in the fight against the pandemic.